Feasibility of RESTORE: An online Acceptance and Commitment Therapy intervention to improve palliative care staff wellbeing. (February 2023) - Finucane, Anne M; Hulbert-Williams, Nicholas J; Swash, Brooke; Spiller, Juliet A; Wright, Brigid; Milton, Libby; Gillanders, David
Background: Acceptance and Commitment Therapy is a form of Cognitive Behavioural Therapy which uses behavioural psychology, values, acceptance and mindfulness techniques to improve mental health and wellbeing. Acceptance and Commitment Therapy is efficacious in treating stress, anxiety and depression in a broad range of settings including occupational contexts where emotional labour is high. This approach could help palliative care staff to manage work-related stress and promote wellbeing. Aim: To develop, and feasibility test, an online Acceptance and Commitment Therapy intervention to improve wellbeing of palliative care staff. Design: A single-arm feasibility trial of an 8-week Acceptance and Commitment Therapy based intervention for staff, consisting of three online facilitated group workshops and five online individual self-directed learning modules. Data was collected via online questionnaire at four time-points and online focus groups at follow-up. Setting/participants: Participants were recruited from Marie Curie hospice and nursing services in Scotland. Results: Twenty five staff commenced and 23 completed the intervention (93%). Fifteen participated in focus groups. Twelve (48%) completed questionnaires at follow-up. Participants found the intervention enjoyable, informative and beneficial. There was preliminary evidence for improvements in psychological flexibility (Cohen's d = 0.7) and mental wellbeing (Cohen's d = 0.49) between baseline and follow-up, but minimal change in perceived stress, burnout or compassion satisfaction. Conclusion: Online Acceptance and Commitment Therapy for wellbeing is acceptable to palliative care staff and feasible to implement using Microsoft Teams in a palliative care setting. Incorporating ways to promote long-term maintenance of behaviour changes, and strategies to optimise data collection at follow-up are key considerations for future intervention refinement and evaluation.